USE OF SOCIAL MEDIA IN ARTS MARKETING: A LITERATURE REVIEW - Chhabra, Neha Kaur; Chaturvedi, D. D. (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Social media has revolutionised the marketing landscape and the art industry is not untouched. The present study explores the utilization of social media for marketing within the art sector, synthesizing various research findings to provide a comprehensive understanding of its impact and effectiveness. By examining diverse studies, the review emphasizes the role of social media platforms as effective tools for promoting art, engaging audiences, and building brands. It covers key themes such as the strategies employed by artists and galleries, the role of visual and interactive content, and the metrics used to gauge success. Additionally, it addresses challenges such as requirement of human and financial resources, dynamic algorithms and social media fatigue. The review further highlights gaps in the existing literature and recommends areas for future research, including the influence of emerging platforms and evolving user behaviours. This synthesis aims to offer valuable insights for art marketers, curators, and scholars seeking to leverage social media effectively in the dynamic landscape of art marketing.